Application of final actions management which behave to the type «motions without a purpose» as a methodical technique for effective motion skills forming in shooters - Калиніченко, О. М.; Лопатьєв, А. О. (Physical Education Theory and Methodology, 2013)
The authors hypothesize that the optimum motor skills of shooters can be formed only if they ability to apply such mechanisms of management final actions which by M. Bernshteyn is classified as «motions without a purpose». The methodical receptions of the use of the special devices which are instrumental in the capture of ability to pass to the optimum mechanisms of management motions of shooter are analyzed. In the article description of author variant of mechanical device «double management» which it is suggested to utilizes for forming of optimum variants motive skills of shooters from a pistol.